Managerial economics - Hirschey, Mark; Bentzen, Eric (Cengage Learning EMEA, 2016)
The economic concepts presented in Managerial Economics show you how to use common sense to understand business and solve managerial problems. This innovative text helps you sharpen your economic intuition. With its unique integrative approach, the text demonstrates that important business decisions are interdisciplinary, illustrating how different functions work together. A basic valuation model is constructed and used as the underlying economic model of the firm; each topic is then related to an element of the value maximization model - a process that shows how management integrates accounting, finance, marketing, personnel and production functions. The text also provides an intuitive guide to marginal analysis and basic economic relations.